Strengthening the image of Marseille through nautical architectural infrastructure: Analysis of the modernisation of the Roucas Blanc Marina for the 2024 Summer Olympics - Sarol, Daria (Research Papers in Economics and Finance, 2025)
Architectural investments in sports infrastructure serve marketing purposes, particularly place branding and city image creation. The article examines the modernisation of the Roucas Blanc facilities, Marseille, for 2024 Summer Olympics nautical events. It discusses tourism and image-related benefits. The study used a mixed method. Firstly, secondary materials, including Marseille’s official project documents and development strategies were collected and analysed. Secondly, field studies with photographic documentation of the modernised Roucas Blanc Marina focused on functionality and architectural solutions. Thirdly, a survey among coaches of the Polish sailing team preparing for the Olympics was conducted. Despite the shortage of respondents, the survey provided expert opinions on the port facilities. The documents confirmed that nautical infrastructure is a cornerstone of Marseille’s promotional strategy. The photographs revealed architecturally and functionally coherent development and facilities well integrated into the surroundings. The coaches appreciated the facility’s modernity and indicated their intention for future training camps there. The study confirmed that the Roucas Blanc Marina modernisation strengthens Marseille’s image and can promote the long-term sports tourism development. The limited survey scope and the scarcity of data following the Games indicates the need for further long-term analyses of the impact these investments have exerted on the city.